The association of healthy lifestyle behaviors with overweight and obesity among older adults from 21 countries - Marconcin, Priscila (2021)
This study aimed to analyze the association of healthy lifestyle behaviors with overweight and obesity among Europeans aged 65+ years. Data were from the 2014 European Social Survey, analyzing 21 countries. Five lifestyle behaviors (physical activity, fruit and vegetable consumption, sleep quality, drinking alcohol, and smoking) were analyzed. Binary logistic regressions were performed. A total of 8938 participants (4099 men) 65 years and older, mean age—73.6 (SD: 6.6) presented prevalence of overweight of 42.3% (95% CI: 41.3 to 43.3) and obesity of 20.9% (95% CI: 20.1 to 21.8). Adopting five healthy behaviors was associated with lower odds of obesity (OR = 0.50, 95% CI: 0.39 to 0.63), but not overweight (OR: 0.93; 95% CI: 0.79 to 1.10). Physical activity (≥5 days/week) was the most protective behavior, reducing by 42% the odds of obesity. Sex moderated the association of fruits and vegetables consumption, alcohol use, and smoking with obesity. Strategies aiming to reduce obesity levels in older adults should focus on the promotion of multiple lifestyle health behaviors, particularly physical activity in order to decrease vulnerability risk in old age.